Clinical Study of Prevalence of Antibiotic Resistance of in Urinary Tract Infection in Children: A 9-year Retrospective, Single Center Experience - Eun Young Seo; Seung Man Cho; Dong Seok Lee; Sung Min Choi; Doo Kwun Kim (Korean Society of Pediatric Nephrology, 2017)
Purpose The aim of this study was to determine the prevalence of antibiotic susceptibility and resistance of Escherichia coli in urinary tract infections (UTIs) in children. Methods We retrospectively reviewed the clinical records of 212 inpatients aged 18 years or younger with UTIs treated at the Pediatric Department of Dongguk University Gyeongju Hospital between January 2008 and December 2016. For comparison, patients were divided into three groups according to age as follows: group 1, ≤1 month; group 2, >1 month to ≤12 months; and group 3, ≥13 months. The antibiotic resistance rates from January 2008 to December 2012 (study period 1) and from January 2013 to December 2016 (study period 2) were analyzed statistically by group. Results As the patient age increased, the antibiotic resistance rate to ampicillin (P=0.013), levofloxacin (P=0.050), piperacillin/tazobactam (TZP) (P<0.001), and trimethoprim/sulfamethoxazole (P=0.002) increased. The frequency of extended spectrum beta-lactamase producing E. coli showed a significant difference from 5 cases (4.6%) in study period 1 and 16 cases (15.8%) in study period 2 (P=0.007). The antibiotic resistance rate of E. coli was compared between the two time periods and we found that the antibiotic resistance rate to cefotaxime was significantly increased from 5.4% to 16.8% (P=0.008) and that to TZP was significantly decreased from 40.5% to 7.9% (P<0.001). Conclusion Over the past 9 years, the resistance rate to cefotaxime has increased but the resistance rate to TZP has decreased. Thus, it is important to continue to investigate the antibiotic resistance rates of bacteria in the community.